(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Child labour continues to be a deep-rooted social and legal issue in India. Despite numerous constitutional safeguards, legislative provisions, and international commitments, the exploitation of children in various forms of labour persists. This research paper delves into the causes, legal framework, and judicial responses concerning child labour in India. It evaluates the effectiveness of the existing laws, analyzes landmark judicial decisions, and suggests reforms for eradicating child labour and ensuring child welfare.